Long cardiac troponin T forms in a healthy reference population - Tuominen, Tuulia; Vasankari, Tuija; Junes, Helea; Salonen, Selma; Teppo, Konsta; Linko-Parvinen, Anna; Pallari, Hanna-Mari; Airaksinen, K.E. Juhani; Wittfooth, Saara (Elsevier BV, 2025)
Background
Cardiac troponin T (cTnT) is an established biomarker in the diagnosis of myocardial infarction (MI). Recent studies show better discrimination between MI and other conditions when measuring only intact or minimally fragmented cTnT forms (long cTnT), compared to current cTnT assays that measure both intact and highly fragmented cTnT forms (total cTnT). This study investigated the long cTnT concentrations in a healthy population.
Methods
Lithium-heparin plasma samples were collected from 314 healthy volunteers aged 21–85 years (59 % female). The samples were analyzed for total cTnT with Roche Elecsys high sensitivity cTnT assay and with a novel upconversion luminescence-based long cTnT assay.
Results
The median (25th-75th percentile) long cTnT concentration of the reference population was 2.0 (1.3–3.0) ng/l. The 99th percentile URL for the long cTnT assay was 7.3 (95 % confidence interval, 5.6–8.4) ng/l. Of the healthy population 98 % had long cTnT levels above the detection limit of the assay (0.4 ng/l). The imprecision (coefficient of variation) of the long cTnT assay at the 99th percentile URL was 5.1 %. While total cTnT was heavily associated with age, especially in the older population, long cTnT remained low regardless of age. Common comorbidities and medications were also associated with the total cTnT concentration but not with the long cTnT concentration.
Conclusions
The long cTnT assay fulfills the requirements for a high sensitivity cTnT assay. Healthy individuals have low long cTnT concentrations regardless of age and common comorbidities.